Precursor-driven acidity enhancement in Titania-modified KCC-1 for efficient n-Hexane hydroisomerization - Mahadi, Bahari; Aishah, Abdul Jalil; Nurul Sahida, Hassan; Madzlan, Abd Aziz; Izzudin, N. M.; Arezudin, A.; Rahman, A. F.A.; Rajendran, Saravanan; Kamarizan, Kidam; Herma Dina, Setiabudi (Elsevier B.V., 2025)
The catalytic activity of titania-loaded fibrous silica (KCC-1) catalysts synthesized using different titania (Ti) precursor compounds was first explored for the hydroisomerization of n-hexane. The Ti crystallite sizes reveal a descending order: TiSO4/KCC-1 (9.70 nm) > Ti-Iso/KCC-1 (4.86 nm) > TiCl4/KCC-1 (3.64 nm), indicating the lower Ti distribution for TiSO4/KCC-1. A decline in surface area is observed as Ti-Iso/KCC-1 (549 m2 g−1) < TiSO4/KCC-1 (599 m2 g−1) < TiCl4/KCC-1 (619 m2 g−1) < KCC-1 (644 m2 g−1), resulted from partial blockage of TiO2 particles and structural disruption of KCC-1 support. The NH3-TPD analysis reveals the total area acid amount of Ti-Iso/KCC-1 surpassed the other Ti-loaded KCC-1 catalysts, attributed to the presence of acidic protons on isopropoxide ligands. Among the n-hexane hydroisomerization catalysts, Ti-Iso/KCC-1 stands out with the most substantial isomer production, achieving a notable 59.7 % yield, followed by TiCl4/KCC-1 (54.5 %) > TiSO4/KCC-1 (54.1 %) > KCC-1 (23.1 %). This trend corresponds with the sequence of total area acid amount from NH3-TPD desorption peaks, highlighting the enhanced isomer activity in Ti-Iso/KCC-1 compared to others due to higher amounts of acidity.